Transforming agricultural research and development systems to meet 21st Century needs for climate action - Hellin, Jon; Fisher, Eleanor; Bonatti, Michelle (Frontiers Media, 2024)
As agricultural researchers, we relate to the multifarious suggested priority research areas, recommendations and critiques of CGIAR and other agricultural research organizations. We believe, however, that discussions to date obscure fundamental and wider aspects about how research is done to ensure that it contributes to the needed radical transformation of food, land and water systems to meet 21st Century needs. We recognize the huge contribution that a plethora of agricultural research and development systems have made and continue to make toward meeting these needs. It is not our intention to question the raison d’être of legions of committed professionals. On the contrary, we seek to make constructive suggestions and provoke discussions that we believe will render these systems even more eﬀective, eﬃcient and impactful. A fundamental ﬁrst step is an urgent and radical transformation in the way that we conceptualize the research process and undertake research.